Cortisol and testosterone accumulation in a low pH recirculating aquaculture system for rainbow trout (Oncorhynchus mykiss) - Mota, Vasco (2018)
Steroids accumulate in recirculating aquaculture system (RAS), although explanatory factors for such accumulation are still poorly explored. This study investigated the effect of water exchange rate and pH in six replicated RAS on the concentration of the stress hormone cortisol in rainbow trout blood plasma and in the holding water and of the sex steroids testosterone, 11-ketotestosterone (11-KT) and 17,20-dihydroxypregn-4-en-3-one (17,20-P) over a 70-day experimental period. Three combinations of water exchange rate and pH were used each treatment, with two replications: (i) high water exchange rate (+/- 1700Lkg(-1) feed) and neutral pH (+/- 7.3), (ii) low water exchange rate (+/- 500Lkg(-1) feed) and neutral pH (+/- 7.3) and (iii) low water exchange rate (+/- 500Lkg(-1) feed) and low pH (+/- 5.8). Plasma cortisol concentrations at day 70 were higher (24.4 +/- 9.5ngmL(-1)) for fish kept at low pH when compared to fish kept at neutral pH (12.0 +/- 0.1 and 8.7 +/- 0.2ngmL(-1)). Water cortisol and testosterone concentrations at day 35 were higher at low pH than at neutral pH, whereas water 11-KT and 17,20-P did not differ among treatments. At day 70, there were no significant differences between low and high pH. These results demonstrate that low pH contributes to increased plasma cortisol concentrations and to its accumulation in water, possibly indicating a stress response to low pH. The higher concentration of testosterone but not of the other sex hormones point to unspecified reproductive effects that need further investigation.